Judicial Activism of the Constitutional Court in Progressive Law Discovery: Limitations, Checks and Balances, and the Threat of Becoming a Positive Legislator - Hasanah, Nur Rizkiah; Irwan Triadi (Yayasan Cahaya Generasi Positif, 2025)
This study examines the judicial activism of Indonesia’s Constitutional Court as a form of progressive law discovery, assessing its implications for the doctrine of separation of powers and the risk of the Court functioning as a positive legislator. Rooted in the civil law tradition, Indonesian judges undertake Rechtvinding to bridge gaps in codified law, a mandate that intensifies under constitutional review. Employing a doctrinal legal research method, the analysis synthesizes statutory texts, case law, and scholarly commentary through hermeneutic and comparative techniques. Two landmark decisions illustrate contrasting approaches: Decision No. 46/PUU-VIII/2010, where the Court created new norms concerning the civil status of children born out of wedlock, and Decision No. 168/PUU-XXI/2023, which exercised procedural activism by issuing legislative orders on the Job Creation Law. Findings reveal a normative dilemma between fulfilling substantive justice and preserving legislative sovereignty. Excessive use of extensive interpretation risks normative incoherence and undermines checks and balances, whereas procedural activism offers a calibrated mechanism to guide legislative reform without overstepping constitutional boundaries. The study proposes codifying interpretive limits, promoting judicial self-restraint, and enhancing legislative responsiveness to maintain coherent jurisprudence and uphold constitutional supremacy. These recommendations aim to fortify Indonesia’s constitutional order by balancing judicial innovation with the integrity of democratic lawmaking.